2018
DOI: 10.3934/microbiol.2018.1.173
|View full text |Cite
|
Sign up to set email alerts
|

Novel roles for two-component regulatory systems in cytotoxicity and virulence-related <em>properties in Pseudomonas aeruginosa</em>

Abstract: The rapid adaptation of the opportunistic bacterial pathogen Pseudomonas aeruginosa to various growth modes and environmental conditions is controlled in part through diverse two-component regulatory systems. Some of these systems are well studied, but the majority are poorly characterized, even though it is likely that several of these systems contribute to virulence. Here, we screened all available strain PA14 mutants in 50 sensor kinases, 50 response regulators and 5 hybrid sensor/reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 49 publications
1
29
0
Order By: Relevance
“…We noted certain similarities between TCS genes involved in the biofilm formation on ETTs (this study) and those reported for biofilm formation on other surfaces such as polystyrene and glass [40,72,73]. This included the regulator of flagellum biogenesis FleR-FleS, phosphate response regulator PhoQ, and AlgR-KinB (Fig.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…We noted certain similarities between TCS genes involved in the biofilm formation on ETTs (this study) and those reported for biofilm formation on other surfaces such as polystyrene and glass [40,72,73]. This included the regulator of flagellum biogenesis FleR-FleS, phosphate response regulator PhoQ, and AlgR-KinB (Fig.…”
Section: Discussionsupporting
confidence: 70%
“…These studies have reported many TCS mutants with increased biofilm biomass. Of these negative regulators previously reported, we found that mutants in 22 genes, pilG, creB, creC, agtR, hsbR, hptB, PA3271, sagS, czcR, parR, PA14_43670 (PA1611), PA14_46370 (PA1396), PA14_52250 (PA0929), gacS, rcsB, cbrA, PA14_63210 (PA4781), gcbA, ntrB, dctB, algZ and algB had increased biofilm biomass on ETT surface [16,40,73,79,92,94,98,99,[101][102][103][104]. In addition, we found six new genes, agtS, cprR, parS, pprA, colR and pmrB with increased biofilm biomass.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Phenotypic screening of transposon mutants revealed that NtrC contributes to swarming motility (Yeung et al, 2009). Furthermore, we previously showed that mutants in ntrB and ntrC demonstrated modestly (∼20%) increased toxicity and substantially reduced adherence to epithelial cells (Gellatly et al, 2018). Here, the pathogenic properties of NtrB and NtrC were further explored.…”
Section: Introductionmentioning
confidence: 94%